Phytochemistry and in vitro Antimicrobial, Antioxydant Activities of Entandrophragma candollei H. - Nnanga NGA, Vandi Deli, Famen NDEL Louis Claire, SIDJUI SIDJUI Lazare, SIKADEU Sandrine, NGUE Samuel Arthur, Toghueo Kouipou Rufin Marie, Nganso DITCHOU Yves Oscar, MPONDO MPONDO Emmanuel (Journal of Applied Pharmaceutical Science, 2016)
The research work was conducted to investigate the in vitro antimicrobial and antioxidant activity of extract of E. candollei (Family-Meliaceae). Phytochemical screening was done. Disc diffusion technique was used for in vitro antibacterial and antifungal screening. Minimal inhibitory concentration of promising extracts was determined by broth microdilution method. The phytochemical screening showed the presence of flavonoids compounds, tannins and saponins. The inhibition diameters were ranging from 7 to 17 mm and Minimum Inhibitory Concentrations (MIC) from 156.25 to 2500 µg/mL. The ethyl acetate and ethanolic extract revealed a high radical scavenging activity with IC50 ranging from 9.1026 to 11.8298 µg/mL. The Ferric reducing power activity was obtained with active concentration ranging from 12.5 to 200 µg/mL. These results suggest that extracts from E. candollei possess antibacterial and antioxidant activities and therefore justifies their usage in traditional medicine for the treatment of various diseases.
Keywords: Entandrophragma candollei, antioxidant, antimicrobial activity.